Competencias del Contador Público de la Universidad del Quindío, requeridas por las organizaciones privadas del sector industrial del departamento del Quindío (2012)
The University of Quindío, in May 1998, made it a priority to meet the CNA requirements concerning quality of higher education, those general requirements relate to: the self-evaluation by the institution measuring the quality of modern education, evaluation by academic peers appointed by the Council who, based on self-assessment and evaluation by the CNA, through previous assessments, resulting in the granting or not accreditation resolution quality.